2017
DOI: 10.1113/ep086537
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of muscle blood flow and oxygen consumption response from exercise using near‐infrared spectroscopy

Abstract: New Findings r What is the central question of this study?Continuous-wave near-infrared spectroscopy, coupled with venous and arterial occlusions, offers an economical, non-invasive alternative to measuring skeletal muscle blood flow and oxygen consumption, but its reliability during exercise has not been established. r What is the main finding and its importance?Continuous-wave near-infrared spectroscopy devices can reliably assess local skeletal muscle blood flow and oxygen consumption from the vastus latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…This study has several limitations. First, we did not directly measure muscle blood flow, but NIRS-determined HbO 2 reflects changes in muscle blood flow (Fadel et al 2004;Hachiya et al 2008;Lucero et al 2018) albeit with an influence of SkBF (Ogoh et al 2014;Hirasawa et al 2015Hirasawa et al , 2016. Muscle blood flow in humans may be evaluated using positron-emission tomography or magnetic resonance imaging (Heinonen et al 2011), but is not feasible during water immersion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has several limitations. First, we did not directly measure muscle blood flow, but NIRS-determined HbO 2 reflects changes in muscle blood flow (Fadel et al 2004;Hachiya et al 2008;Lucero et al 2018) albeit with an influence of SkBF (Ogoh et al 2014;Hirasawa et al 2015Hirasawa et al , 2016. Muscle blood flow in humans may be evaluated using positron-emission tomography or magnetic resonance imaging (Heinonen et al 2011), but is not feasible during water immersion.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we hypothesized that acute immersion in carbonated, but not tap water, at 38°C increases muscle blood flow. We evaluated PA blood flow by duplex ultrasound and gastrocnemius muscle oxyhemoglobin concentration (HbO 2 ) using near-infrared spectroscopy (NIRS) as an index of muscle blood flow (Fadel et al 2004;Hachiya et al 2008;Lucero et al 2018) during acute immersion of both lower legs in carbonated and tap water at 38°C.…”
Section: Introductionmentioning
confidence: 99%
“…For each time point (10 min, 90 min, 170 min, post-), data were averaged over 30 s and expressed relative to supine baseline. Our laboratory has previously reported that the Portalite device is able to monitor changes in tHb with acceptable validity and reliability (intraclass correlation, ICC, range: 0.75-0.98; Lucero et al, 2017;Stone, Fryer, Ryan, & Stoner, 2016) and changes in TSI with acceptable reliability (ICC: 0.7-0.9; Lucero et al, 2017).…”
Section: Calf Blood Volumementioning
confidence: 99%
“…Additionally, the rate of change in total hemoglobin following venous occlusion is used to determine skeletal muscle microvascular blood flow. 55,56 Briefly, a tourniquet, placed upstream from the site of interest, is inflated to a subdiastolic pressure (e.g., 100 mmHg) to occlude venous outflow while minimally obstructing arterial inflow. Blood flow is then calculated by evaluating the linear increase in total hemoglobin during the first few seconds of the occlusion.…”
Section: Nirsmentioning
confidence: 99%